Lower uric acid and adequate hydration are associated with lower risk of febrile neutropenia following autologous bone marrow transplantation in patients with lymphoma - Nejati, Babak; Kourehpaz, Zohreh; Dolatkhah, Roya; Varshochi, Mojtaba; Farmani, Maryam; Parviz, Alireza (Journal of Medical Science, 2023)
Background. Despite the promising results of autologous bone marrow transplantation (BMT) in patients with lymphoma, infectious complications limit its positive outcomes. This study evaluated the incidence and associated factors of febrile neutropenia (FN) following BMT in patients with lymphoma.Materials and methods. The study consecutively included 147 patients with lymphoma who were candidates for BMT. Clinical and laboratory results were recorded, and after BMT, the occurrence of FN was investigated through the daily evaluation of neutrophil count and body temperature.Results. On average, FN occurred in 91 patients (61.9%) after 12.77 ± 2.45 days after BMT.  Lower fluid balance was associated with a higher risk of FN (lowest adjusted odds ratio [OR] at day -2 = 0.602, 95% confidence interval [CI] = 0.299 – 0.870, p-value = 0.007). The higher uric acid level was associated with a higher risk of FN (highest adjusted OR at day -10 = 1.617, 95% CI = 1.328 – 1.963, p-value = 0.035). LDH was also positively correlated with FN (highest adjusted OR at day 0 = 1.501, 95% CI = 1.198 – 2.104, p-value = 0.004).Conclusions. Adequate hydration of the patients is of paramount importance for preventing FN in patients who receive BMT. Furthermore, uric acid and LDH could be considered in future studies for the risk stratification of FN.
Keywords: febrile neutropenia; autologous bone marrow transplantation; lymphoma; infection